The civic potential of memes and hashtags in the lives of young people. Issue 5 (2nd September 2020) - Mihailidis, Paul
ABSTRACT: Young people today are immersed in digital culture: often considered savvy navigators of online ecosystems and adept at using everyday technologies to share, create and express. These technologies are often seen as social and personal tools instead of spaces for meaningful participation. This paper shares the results of an investigation in young people's attitudes towards popular social communication modalities – memes and hashtags – for civic purposes. The study employs Emerging Citizens: a suite of digital literacy tools and accompanying learning content that teach people of all ages how to critique and create hashtags and memes. This inquiry explores how young people perceive memes and hashtags as relevant avenues for civic expression, and the impact that a digital literacy intervention can have on youth attitudes. An analysis of the student experience using the Emerging Citizens tools and reflection of their creations finds that digital literacy interventions impact young people's perceptions of popular social modalities for civic impact.